Pharmacokinetic interactions among imatinib, bosentan and sildenafil, and their clinical implications in severe pulmonary arterial hypertension. (1st June 2015) - Renard, Didier; Bouillon, Thomas; Zhou, Ping; Flesch, Gerard; Quinn, Debbie
<x xml:space="preserve">Abstract</x> Aims This study characterized the population pharmacokinetics (PK) of imatinib in patients with severe pulmonary arterial hypertension (PAH), investigated drug–drug interactions (DDI) among imatinib, sildenafil and bosentan, and evaluated their clinical implications. Methods Plasma concentrations of imatinib, bosentan and sildenafil were collected in a phase III study and were used to characterize the PK of imatinib in this population. DDIs among the three drugs were quantified using a linear mixed model and log‐transformed drug concentrations. Results The population mean estimates of apparent clearance (CL/F) and volume (V/F) were 10.8 l h–1 (95% CI 9.2, 12.4 l h–1) and 267 l (95% CI 208, 326 l), respectively. It was estimated that sildenafil concentrations increased, on average, by 64% (95% CI 32%, 103%) and bosentan concentrations by 51% (95% CI 12%, 104%), in the presence of imatinib. Despite increased concentrations of co‐medications, treatment differences between imatinib and placebo for change in 6 min walk distance and pulmonary vascular resistance were relatively constant across the entire concentration range for sildenafil and bosentan. Overall, higher concentrations of imatinib and bosentan were not associated with increasing liver enzymes (serum glutamic oxaloacetic transaminases [SGOT]/serum glutamic‐pyruvic transaminase [SGPT]). Conclusions Population PKs of imatinib in patients with severe PAH were found comparable with those of patients with chronic myeloid leukemia. Imatinib was found effective regardless of the co‐medications and showed intrinsic efficacy beyond merely elevating the concentrations of the co‐medications due to DDIs. There was no evidence of increased risk of liver toxicity upon co‐administration with bosentan.